Quality Analysis of Fresh Milk Based on Specific Gravity Parameters at CV Cita Nasional in Central Java, Indonesia - Rahmawati, Farida Dwi; Juwitaningtyas, Titisari (The Indonesian Institute of Science and Technology Research, 2024)
In maintaining the quality of milk produced, it is necessary to supervise and control quality. One important aspect is controlling the specific gravity value of fresh milk. The specific gravity parameter of fresh milk is one of the determinants of whether the milk can be accepted or rejected as raw material. In addition, it is also a determining factor in determining the selling price of milk. To determine the quality control of the specific gravity of fresh milk, the control chart analysis method is used. The results of the analysis that have been carried out from various KUDs obtained the average specific gravity of fresh milk from Capita Farm KUD which is 1.0295 g / mL; the average specific gravity of fresh milk from KUD Cepogo is 1.0265 g/mL; the average specific gravity of fresh milk from Andini KUD is 1.0266 g/mL; the average specific gravity of fresh milk from Getasan KUD is 1.0268 g/mL, and the average specific gravity of fresh milk from Boyolali Kota KUD is 1.0292 g/mL. The specific gravity value of fresh milk supplied from various KUD can be concluded that the specific gravity value meet the company's quality standards, SNI, and existing literature so it is said that the specific gravity of fresh milk in CV Cita Nasional is in control, and can be accepted as raw material for making pasteurized milk.